2015
DOI: 10.1371/journal.pone.0124056
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of D-Threonine Aldolase from Alcaligenes xylosoxidans Provides Insight into a Metal Ion Assisted PLP-Dependent Mechanism

Abstract: Threonine aldolases catalyze the pyridoxal phosphate (PLP) dependent cleavage of threonine into glycine and acetaldehyde and play a major role in the degradation of this amino acid. In nature, L- as well as D-specific enzymes have been identified, but the exact physiological function of D-threonine aldolases (DTAs) is still largely unknown. Both types of enantio-complementary enzymes have a considerable potential in biocatalysis for the stereospecific synthesis of various β-hydroxy amino acids, which are valua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 41 publications
1
19
1
Order By: Relevance
“…The recent publication of the crystal structure of a bacterial DTA from A. xylosoxidans identified a metal-binding site in the active site, which was consistent with previous observations that divalent metal ions are essential for DTA activity (PDB entry 4v15; Uhl et al, 2015). However, the current limited structural information on DTAs makes it difficult to understand the structural differences between bacterial and eukaryotic DTAs and to develop stereoselective d-or d-allothreonine aldolases.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…The recent publication of the crystal structure of a bacterial DTA from A. xylosoxidans identified a metal-binding site in the active site, which was consistent with previous observations that divalent metal ions are essential for DTA activity (PDB entry 4v15; Uhl et al, 2015). However, the current limited structural information on DTAs makes it difficult to understand the structural differences between bacterial and eukaryotic DTAs and to develop stereoselective d-or d-allothreonine aldolases.…”
Section: Introductionsupporting
confidence: 79%
“…Previous studies indicated that the bacterial DTAs from A. xylosoxidans and Arthrobacter sp. were active as monomers (Liu, Odani et al, 2000;Kataoka et al, 1997), but the crystal structure of DTA from A. xylosoxidans was predicted to be a stable dimer in solution (Uhl et al, 2015). Our results indicate that the assembly of CrDTA molecules was similar to that of bacterial DTAs.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The classic member of this family is L-serine hydroxymethyl transferase (SHMT), 79 involved in the one-carbon cycle associated with pyrimidine biosynthesis, a three-enzyme pathway in which the other two enzymes are targeted by the clinical chemotherapeutics 5-fluorouracil (thymidylate synthase) and methotrexate (dihydrofolate reductase - DHFR). More recently, PLP dependent aldolases for L-threonine, 80 D-threonine, 81 phenylserine 82 and α-methylserine, 83 with a number of these demonstrating considerable side chain tolerance. 84 Thus, the chemistry presented here is expected to be enabling tool across a broad spectrum of chemical biological studies.…”
Section: Discussionmentioning
confidence: 99%
“…The first crystal structure of d -specific TAs was published recently by Gruber et al for the d TA from Alcaligenes xylosoxidans (axDTA) (Uhl et al 2015 ). DTA belongs to the alanine racemase family of PLP-dependent enzymes (fold type III), and its structure is different from l -specific TAs.…”
Section: Structure Catalytic Mechanism and Mutagenesis Studiesmentioning
confidence: 99%